2004
DOI: 10.1523/jneurosci.0477-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptor-Mediated Oligodendrocyte Toxicity in Periventricular Leukomalacia: A Protective Role for Topiramate

Abstract: Periventricular leukomalacia is a form of hypoxic-ischemic cerebral white matter injury seen most commonly in premature infants and is the major antecedent of cerebral palsy. Glutamate receptor-mediated excitotoxicity is a predominant mechanism of hypoxic-ischemic injury to developing cerebral white matter. We have demonstrated previously the protective effect of AMPA-kainate-type glutamate receptor blockade in a rodent model of periventricular leukomalacia. The present study explores the therapeutic potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
273
0
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(295 citation statements)
references
References 55 publications
(97 reference statements)
13
273
0
9
Order By: Relevance
“…We have shown that white matter and developing OLs are vulnerable to HI insult at P6 in our rat model of PVL (23,24). As previously described, the majority of OLs at P6 in the periventricular white matter and cortex are O4 and O1 positive and not myelin basic protein (MBP) expressing (21,25).…”
Section: Nkcc1 Is Expressed On Developing Ols and Neurons In The Immasupporting
confidence: 69%
“…We have shown that white matter and developing OLs are vulnerable to HI insult at P6 in our rat model of PVL (23,24). As previously described, the majority of OLs at P6 in the periventricular white matter and cortex are O4 and O1 positive and not myelin basic protein (MBP) expressing (21,25).…”
Section: Nkcc1 Is Expressed On Developing Ols and Neurons In The Immasupporting
confidence: 69%
“…In animal models of cerebral ischemia, TPM reduced the severity of cerebral damage either alone [5][6][7][8] or with hypothermia. 9 The neuroprotective mechanisms of TPM action appear related not only to glutamate a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and kainate receptors inhibition, 11,[27][28][29][30] but also to inhibition of Na + channels, 31 high voltageactivated calcium currents, 4 carbonic anhydrase isoenzymes, 32 and mitochondrial permeability transition pore. 19 Hypothermia, conversely, might enhance post-ischemic glutamate reuptake 33 , and suppress nitric oxide synthase, oxidative stress, apoptosis, and inflammatory cascades.…”
Section: Resultsmentioning
confidence: 99%
“…TPM has neuroprotective properties against hypoxic ischemic brain damage, both in vitro and in animal models, and was included in neuroprotective strategies for ischemic stroke [4][5][6][7][8][9][10][11] and neonatal hypoxic-ischemic cerebral injury. 12 Several studies have demonstrated the therapeutic effects of whole-body or selective head cooling to treat asphyxiated newborns.…”
mentioning
confidence: 99%
“…A hypoxic/ischemic model of PVL in the rat at P7 has been previously established 3 . This model is unique in that it resembles PVL in premature infants.…”
Section: Discussionmentioning
confidence: 99%